One pot Aziridation of 2,3-trans Stilbene with Chloramine T derivatives in the presence of catalyst phenyltrimethyl Ammonium Tribromide - Joshi, Susan (Journal of Nepal Chemical Society, 2013)
Phenyltrimethyl ammonium tribromide is an excellent source of bromine which was found to be an efficient catalyst for aziridination of 2,3-trans stilbene utilizing Chloramine T derivatives as a practical nitrogen source. Chloramine T derivatives were examined and were found to give the corresponding trans-2,3-diphenyl-N-arylsulfonyl aziridines in good yields. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9277 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 121-125 Uploaded date: 12/6/2013